2003
DOI: 10.1046/j.1365-2362.2003.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Individuals at increased coronary heart disease risk are characterized by an impaired microvascular function in skin

Abstract: Increased CHD risk is associated with an impaired endothelium-dependent vasodilatation and capillary recruitment in skin, suggesting that microvascular function in skin is a valid model to study the relationships between cardiovascular risk factors and microvascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
169
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(183 citation statements)
references
References 46 publications
8
169
1
5
Order By: Relevance
“…Recent studies have indicated that changes in the cutaneous microvasculature often mirror changes in vessels of different size (Debbabi et al, 2010) and in other vascular beds, such as the coronary microcirculation (Khan et al, 2008). In fact, increasing evidence indicates that the cutaneous microcirculation can serve as a representative model to examine mechanisms of vascular function and dysfunction that occur on a systemic level (Holowatz et al, 2008;IJzerman et al, 2003).…”
Section: In Vitro Vascular Modelsmentioning
confidence: 99%
“…Recent studies have indicated that changes in the cutaneous microvasculature often mirror changes in vessels of different size (Debbabi et al, 2010) and in other vascular beds, such as the coronary microcirculation (Khan et al, 2008). In fact, increasing evidence indicates that the cutaneous microcirculation can serve as a representative model to examine mechanisms of vascular function and dysfunction that occur on a systemic level (Holowatz et al, 2008;IJzerman et al, 2003).…”
Section: In Vitro Vascular Modelsmentioning
confidence: 99%
“…The role of impaired microvascular haemodynamics is increasingly being recognised in the pathogenesis of sub-sequent vascular target organ damage [7,8]. This may, in part, represent shared risk factors; however, the association remains when these are adjusted for, indicating that microvascular injury may occur on the mechanistic pathway between risk factors and vascular target organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…A pele é facilmente acessível [1] e potencialmente representativa [2] para a avaliação dos mecanismos de função e disfunção da microcirculação periférica [3][4][5] em particular quando são usadas tecnologias não invasivas, como a Fluxometria por Laser Doppler (FLD). A FLD está entre as tecnologias mais amplamente utilizadas para este propósito [6] , fornecendo um sinal complexo que pode ser decomposto em componentes com intervalos de frequência característicos, por meio de ferramentas de análise espectrais, tais como a transformada rápida de Fourier, a modelação autorregressiva e a análise de ôndula [7] .…”
Section: Introductionunclassified
“…The skin is easily accessible [1] and potentially representative [2] for the evaluation of peripheral microcirculation function and dysfunction mechanisms [3][4][5] , in particular when noninvasive technologies such as Laser Doppler Flowmetry (LDF) are used. LDF is among the most widely employed technologies for this purpose [6] , providing a complex signal which can be decomposed into components with characteristic frequency ranges by means of spectral analysis tools, such as the fast Fourier transform, autoregressive modelling and wavelet analysis [7] .…”
Section: Introductionmentioning
confidence: 99%